TEN-YEAR EXPERIENCE OF SURGICAL TREATMENT OF GOITER - Ковальов, О.П.; Кравців, М.І.; Люлька, О.М.; Ляховський, В.І.; Дудченко, М.О.; Нємченко, І.І. (World of Medicine and Biology, 2014)
The analysis of medical records of 468 patients has been made. They were operated on for goitre in the Department of Surgery № 2 in the 2-nd Local Clinical Hospital of Poltava during 2004 - 2013. Among them there were 58 male and 410 female. The average age of the patients was 58,6 ± 5,48 years old. Surgical access and the amount of surgery was chosen on the basis of data of the preoperative examination. The access, which we use to operating on the thyroid gland is anatomically justified, provides the necessary exposition of the organ, good postoperative wound healing and cosmetic effect. Extrafascial technique of thyroid gland resection provides bloodlessness and radicality of surgery. The experience of surgical interventions can improve the results of surgical treatment with reducing the number of postoperative complications. The mentioned above findings show that used approaches are effective and safe enough to the treatment of various forms of goiter.